Construction of strontium tantalate homo-semiconductor composite photocatalysts with a tunable type II junction structure for overall water splitting. Issue 12 (9th May 2018) - Sun, Feng; Wang, Ping; Yi, Zhouxiang; Wark, Michael; Yang, Junhe; Wang, Xianying
Abstract : The presence of at least two different strontium tantalates with a type II junction structure for efficient photocatalytic overall water splitting. Abstract : A series of phase-controlled and composition-tuned strontium tantalate homo-semiconductor composite photocatalysts were fabricated by adjusting the initial atomic ratio of Ta/Sr precursors for synthesis. A strong correlation between the phase compositions and the photocatalytic activities for hydrogen evolution was demonstrated, which can be attributed mainly to the significantly improved photogenerated charge carrier separation via interfacial type II junctions. Without any co-catalysts, finely phase-tuned composites, namely Sr5 Ta4 O15 /Sr2 Ta2 O7, Sr5 Ta4 O15 /Sr2 Ta2 O7 /SrTa4 O11 and Sr2 Ta2 O7 /SrTa4 O11, exhibited approximately 20, 38 and 76 times, respectively, higher H2 production rates from aqueous methanol solutions than pure Sr5 Ta4 O15 . Furthermore, by modification with a 1 wt% NiO co-catalyst, both the photocatalytic overall water splitting (OWS) activities and stabilities of the composites were remarkably improved for the simultaneous evolution of H2 and O2 in a nearly stoichiometric ratio. The highest activity with a corresponding photon efficiency of up to 64% was achieved for NiO deposited on Sr2 Ta2 O7 /SrTa4 O11 . The study on the feasibility of the strategy for fabricating homo-semiconductor composites will open up a direction to exploit new high-performance photocatalysts for hydrogen production and OWS.